Three-phase three-level nine switches inverter employing space vector modulation - Ahmed, M.E.; Mekhilef, Saad (2008)
This paper studies the space vector pulse width modulation technique (SVPWM) for the three-phase threelevel nine switches voltage source inverter. The proposed inverter is based on the two level inverter topology where it consists of a main inverter switches Q1, Q2, Q 3, Q4, Q5, and Q6, an auxiliary three bidirectional switches S1, S2, and S3 and two capacitor banks C1, and C2. Ideal switches and diodes will be assumed and the dc bus capacitor bank voltages fluctuations will be absent. The effectiveness of the SVPWM control scheme will be verified by the simulations results in the worst case where two very low switching frequencies values of 1 kHz and 5 kHz will be considered. Open loop controller experimental measurements at 1 kHz switching frequency will be provided.